Graphene based nano-antenna for wireless communication systems at terahertz band - Singh, Raj Kumar; Mamta, Kumari; Kumar, Dhirendra (Institute of Advanced Engineering and Science, 2025)
The need for nano-antennas with decreased size and the capacity to operate at mid-infrared frequencies to enable adequate coverage of signal is being investigated. In this paper, we present graphene-based nano-antenna and analysed at the resonating frequency 33 THz using gallium arsenide material as a substrate having dielectric constant 11.35 and a loss tangent of 5.6×10-4 for terahertz (THz) frequency. The height of substrate is optimized to 108 nm and in-plane dimension being 1,700×1,400 nm. Graphene was used as a rectangular patch with dimension 850×450×5 nm and ground having chemical potential=1.4 eV, and relaxation time=1 ps, to achieve high gain and bandwidth. Impact of slot width variation on the antenna parameters have been reported in terms of reflection coefficient (S11), voltage standing wave ratio (VSWR), radiation pattern and gain. Reported beam width being 90.4° for both electric and magnetic planes. Proposed antenna achieved a return loss of -18.38 dB, VSWR less than 2, indicating good match with load, highest gain of 8.8 dBi and bandwidth of 500 GHz at the target resonance frequency making it suitable for 5G/6G mm wave wireless communication.